2014
DOI: 10.1116/1.4900719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of surface morphology of Si substrate on performance of Si/ZnO heterojunction devices grown by atomic layer deposition technique

Abstract: Articles you may be interested inImpact of annealing on the chemical structure and morphology of the thin-film CdTe/ZnO interface J. Appl. Phys. 116, 024312 (2014); 10.1063/1.4890235 CdS nanofilms: Effect of film thickness on morphology and optical band gap Growth morphology and electrical/optical properties of Al-doped ZnO thin films grown by atomic layer deposition J. Vac. Sci. Technol. A 30, 021202 (2012); 10.1116/1.3687939Texture vs morphology in ZnO nano-rods: On the x-ray diffraction characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The lattice mismatch is not always considered essential to influence on the growth mechanism and film quality, while the synthesizing method has curtail effect on film crystalline quality 20,21 and its behaviors, this phenomena has been observed and studied very well in previous works using several deposition techniques 8,12 . For very thin films the properties will be dominated by the several materials used in interface favorite the nanostructural nucleation and play a catalyst role 7 , which has been observed recently 22 . On the other hand, the optical, sensing and electrical 7 properties have been sensible to the doped dose as well as metal nature like Cu, Zn, Pb or Ag 5 .…”
Section: Introductionmentioning
confidence: 83%
“…The lattice mismatch is not always considered essential to influence on the growth mechanism and film quality, while the synthesizing method has curtail effect on film crystalline quality 20,21 and its behaviors, this phenomena has been observed and studied very well in previous works using several deposition techniques 8,12 . For very thin films the properties will be dominated by the several materials used in interface favorite the nanostructural nucleation and play a catalyst role 7 , which has been observed recently 22 . On the other hand, the optical, sensing and electrical 7 properties have been sensible to the doped dose as well as metal nature like Cu, Zn, Pb or Ag 5 .…”
Section: Introductionmentioning
confidence: 83%
“…To solve this problem, many researchers have investigated Sibased heterojunction photocatalysts that not only protect the silicon from water, but also promote the separation of the photogenerated electrons and holes [11][12][13]. Si-based heterojunctions can be constructed by several methods such as electrodeposition [14,15], atomic layer deposition [16,17], and chemical vapor deposition [18]. In particular, the coupling of Cu 2 O with Si in a heteronjunction has attracted great attention in recent years because Cu 2 O is one of the few p-type direct band gap semiconductors with a band gap of 2.0 eV that can serve as an efficient photocatalytic material [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a controlled semiconductors (ZnS, ZnO and SnO2) nanostructure plays a crucial role in optoelectronic devices performance. Hazra et al [26] demonstrated the core-shell structure of ZnO films deposited on silicon nanowires (NW) heterostructures with SiNWs as core and ZnO thin film as shell prepared by Atomic Layer Deposition.…”
Section: Introductionmentioning
confidence: 99%